(untitled) (Nepal Medical College Journal, 2020)
The purpose of this study was to evaluate the location and pattern of visual field defects as measured by Humphrey Field Analyzer (HFA 24-2) in newly diagnosed primary open angle glaucoma (POAG) attending tertiary care hospital. This was a cross sectional, descriptive study. One hundred and four eyes of 52 patients who fulfilled the inclusion criteria during one year were included. They were classified as mild, moderate and severe glaucoma according to severity. Paracentral scotoma in superotemporal and superonasal region was the most frequent visual field defect observed in mild glaucoma. Superior arcuate defect and double arcuate defect was commonly seen among moderate and severe stages of POAG respectively. There was a significant association between severity of glaucoma and pattern of visual field defect (p=0.000). The superior hemifield was affected twice more than the inferior hemifield in newly diagnosed cases of POAG.